2010
DOI: 10.1262/jrd.10-069h
|View full text |Cite
|
Sign up to set email alerts
|

Time-Lapse Videomicrographic Observations of Blastocyst Hatching in Cattle

Abstract: Abstract. Morphological changes of cultured bovine blastocysts during hatching were observed using time-lapse videomicrography in order to investigate the patterns of the hatching process that occurred in the blastocysts and to determine whether the hatching patterns differed between blastocysts developed from fresh and cryopreserved embryos. Compacted morulae (CMs) were collected from superovulation-treated Japanese Black and Holstein dairy cattle and cultured in a medium in a CO2 culture chamber equipped wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…On the other hand, embryos with good morphology, which are chromosomally normal, may fail to differentiate into blastocysts [12]. To achieve a high implantation rate, transferable embryos are selected by considering various parameters beyond morphokinetics, such as the duration of oocyte activation [13], first cell division [14,15,16,17], pronuclear (PN) scoring [18], presence of evenly cleaved blastomeres [19], degree of fragmentation [20, 21], cleavage pattern [9], contraction pattern, and time to hatching [22, 23]. …”
mentioning
confidence: 99%
“…On the other hand, embryos with good morphology, which are chromosomally normal, may fail to differentiate into blastocysts [12]. To achieve a high implantation rate, transferable embryos are selected by considering various parameters beyond morphokinetics, such as the duration of oocyte activation [13], first cell division [14,15,16,17], pronuclear (PN) scoring [18], presence of evenly cleaved blastomeres [19], degree of fragmentation [20, 21], cleavage pattern [9], contraction pattern, and time to hatching [22, 23]. …”
mentioning
confidence: 99%
“…This is globally in accord with previous reports that used comparable culture systems without cells (20–31%, Shirazi et al, ; 0–29%, Schmaltz‐Panneau et al, ; 41 ± 4.5%, Lopera‐Vasquez et al, ; 48 ± 9%, Lopera‐Vasquez et al, ). However, embryo re‐expansion may be difficult to evaluate because, over time after warming, blastocysts often show repeated collapse and re‐expansion (Maezawa et al, ; Niimura et al, ). Moreover, the duration of the re‐expansion process, if any, is highly variable among blastocysts (Ebner et al, ; Niimura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 2 Developmental rates of bovine blastocysts exposed in vitro to to intraoviductal concentrations of progesterone, estradiol, cortisol, or a combination of all at Day 8 (Maezawa et al, 2014;Niimura et al, 2010). Moreover, the duration of the re-expansion process, if any, is highly variable among blastocysts (Ebner et al, 2017;Niimura et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Niimura et al [25] showed that there is a relationship between the hatching patterns of blastocysts and the development of embryos after transfer, and that a large slit in the zona pellucida contributes to hatching in cattle blastocysts. This could be the theoretical basis for the clinical use of AH.…”
Section: Discussionmentioning
confidence: 99%